My Quiz is Better or It Takes a Semester to Build a Quiz - Freddie Bowles (The Advocate, 2011)
Introduction: Learning by doing appeals to many teachers and students who enjoy the practical application of new knowledge. When learners are able to demonstrate the upper levels of Bloom's taxonomy - application, synthesis, evaluation - the students almost assuredly have demonstrated an "enduring understanding" of the content material.